3D printing of bird’s body surface topography features - Tan, Winston Ming Hui (2018)
In spite of birds being animals, they possess unique anatomic characteristics that distinguish them from other animals which allow most of its species to fly. Bird flight had inspired humans to invent the first powered aircraft in 1903 and mankind has continued to look for ways to make the flying machines more efficient by drawing ideas from the different features of the bird anatomy. The feasibility of replicating the features found on the bird’s body by 3D printing will be looked into. This report aims to investigate whether the topography of a bird’s body will aid in reducing aerodynamic drag. The body of bird specimens had been 3D scanned to obtain the topography and then subsequently replicated the surface features by 3D printing them. 3D printed parts had been tested in NTU’s closed loop wind tunnel. The findings showed the effectiveness of the bird’s body in reducing drag.